1995
DOI: 10.1073/pnas.92.3.699
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular immunization of human fetal cord blood stem/progenitor cells with a ribozyme against human immunodeficiency virus type 1.

Abstract: Successful treatment of human immunodeficiency virus infection may ultimately require targeting of hematopoietic stem cells. Here we used retroviral vectors carrying the ribozyme gene to transduce CD34+ cells from human fetal cord blood. Transduction and ribozyme expression had no apparent adverse effect on cell differentiation and/or proliferation. The macrophage-like cells, differentiated from the stem/progenitor cells in vitro, expressed the ribozyme gene and resisted infection by a macrophage tropic human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 25 publications
5
59
0
2
Order By: Relevance
“…Delivery of anti-HIV ribozyme, dominant negative proteins, or decoys to CD34+ cells partially protected progeny MDMs from HIV replication. 47,[49][50][51][52] Recently, lentivirus vectors used to deliver RNAi against CCR5 were reported to transduce PBMC with low efficiency, and partially protect them from HIV replication. 53 We have found that rSV40 delivery of RNAi may be highly effective in protecting MDMs from R5-tropic HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of anti-HIV ribozyme, dominant negative proteins, or decoys to CD34+ cells partially protected progeny MDMs from HIV replication. 47,[49][50][51][52] Recently, lentivirus vectors used to deliver RNAi against CCR5 were reported to transduce PBMC with low efficiency, and partially protect them from HIV replication. 53 We have found that rSV40 delivery of RNAi may be highly effective in protecting MDMs from R5-tropic HIV.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies on PUCB CD34 + cells have indicated that retrovirus-transduced genes can be introduced into 12-95% of progenitor cells. 9,[11][12][13] In vivo animal studies using SCID mouse models have demonstrated that CD34 + cells derived from PUCB could be successfully engrafted. 14 These promising data have recently led to the initiation of a human gene therapy trial using PUCB-derived CD34 + cells for adenosine deaminase deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…9 Colony formation of Table 3 Clonogenic formation of transduced CD34 + cells derived from normal, HIV-1-exposed and HIV-1-infected infants…”
Section: Ribozyme Transduction and Expression In Transduced Cellsmentioning
confidence: 99%
See 2 more Smart Citations